Modified polytetrafluoroethylene fine powder and method for producing modified polytetrafluoroethylene, and porous membrane using the same

JP2026165811APending Publication Date: 2026-10-14CHEMOURS MITSUI FLUOROPRODUCTS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2025058407
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0009】 本発明によって、 ·小孔径であり、かつ高気孔率であるPTFE多孔膜の原料として好適な変性PTFEファインパウダー、 ·そのPTFE水性乳化重合方法、 ·PTFEファインパウダーから得られるPTFE多孔膜 が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165811000001
    Figure 2026165811000001
  • Figure 2026165811000002
    Figure 2026165811000002
  • Figure 2026165811000003
    Figure 2026165811000003
Patent Text Reader

Abstract

This invention provides a modified polytetrafluoroethylene fine powder suitable for producing polytetrafluoroethylene porous membranes with small pore size and high porosity. [Solution] The reaction temperature and the ratio of the initiator addition rate (mmol / min) at the start of tetrafluoroethylene polymerization to the volume (L) of the aqueous polymerization medium are adjusted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a modified polytetrafluoroethylene fine powder suitable for producing a polytetrafluoroethylene porous membrane having a smaller pore size and a high porosity. The present invention also relates to a method for producing the modified polytetrafluoroethylene for the purpose above.

Background Art

[0002] Polytetrafluoroethylene (PTFE) is utilized in various fields due to its excellent heat resistance, chemical resistance, water repellency, weather resistance and low dielectric constant. Since PTFE is easily made porous by stretching, many PTFE porous membranes with various properties and production methods thereof have been invented so far. For example, in semiconductor manufacturing processes, PTFE porous membranes have been used as filters for removing foreign matters (particularly nano-level fine foreign matters called particles) in various chemical solutions. With the progress of miniaturization of semiconductor processes, more excellent particle removal performance is required. Therefore, a PTFE porous membrane that is finer (smaller in pore size), has a high porosity and is excellent in liquid permeability is demanded. In addition, strength such as breaking strength is also required for PTFE porous membranes.

[0003] For example, Patent Document 1 describes a method in which a membrane not subjected to heat treatment of PTFE or modified PTFE is obtained, heated to achieve a specific crystal melting heat ratio, stretched in one direction, and then stretched in a direction 90 degrees different therefrom. Furthermore, Patent Document 2 describes the use of modified PTFE obtained by copolymerizing tetrafluoroethylene units and perfluorobutylethylene units in a specific way in the production of PTFE porous membranes. Patent Documents 3 to 5 also describe the use of modified PTFE obtained by copolymerizing tetrafluoroethylene (TFE) units and perfluoroalkylethylene (PFAE) units in the production of PTFE porous membranes. Patent Document 3 describes the use of a specific fluorine-containing emulsifier; Patent Document 4 describes the use of a polymerization initiator and a specific fluorine-containing anionic surfactant; and Patent Document 5 describes that the modified PTFE has a specific value for its thermal instability index and a specific area for its differential heat curve. Furthermore, it has been proposed to employ specific temperature conditions when manufacturing PTFE that will be stretched (Patent Documents 6 and 7).

[0004] In fields other than semiconductor processing, there is a widespread demand for PTFE films with smaller pore sizes than conventional films. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 2022-117687 [Patent Document 2] Special Publication No. 2005-506405 [Patent Document 3] International Patent Application Publication No. 2011 / 055824 [Patent Document 4] International Patent Application Publication No. 2017 / 030094 [Patent Document 5] International Patent Application Publication No. 2024 / 019010 [Patent Document 6] Japanese Patent Publication No. 2000-143707 [Patent Document 7] Japanese Patent Publication No. 2000-143727 [Overview of the project] [Problems that the invention aims to solve]

[0006] The object of the present invention is to provide a fine powder of modified PTFE suitable for providing PTFE porous membranes with small pore sizes, and to provide a novel method for producing such modified PTFE. [Means for solving the problem]

[0007] As a result of diligent research to solve the above problems, we discovered that the ratio of the initiator addition rate (mmol / min) at the start of polymerization to the volume (L) of the aqueous polymerization medium greatly affects the performance of the resulting PTFE fine powder and the PTFE porous membrane obtained using it, leading to the completion of the present invention.

[0008] in particular, 1. A modified polytetrafluoroethylene (PTFE) fine powder containing tetrafluoroethylene (TFE) and 0.03 to 0.50 mol% perfluoroalkylethylene (PFAE), characterized in that the tensile strength of the heat-stretched PTFE bead is 25 N or more. 2. Modified PTFE fine powder as described in item 1 above, having a standard specific gravity (SSG) of 2.150 or less. 3. Modified PTFE fine powder as described in item 1 above, having an average primary particle size of 150-200 nm. 4. A modified polytetrafluoroethylene porous membrane comprising tetrafluoroethylene (TFE) and perfluoroalkylethylene (PFAE), wherein the modified polytetrafluoroethylene porous membrane comprises the modified PTFE fine powder described in item 1 above. 5. A method for aqueous emulsion polymerization of perfluoroalkylethylene (PFAE)-modified polytetrafluoroethylene (PTFE), wherein the ratio of the initiator addition rate (mmol / min) at the start of polymerization to the volume (L) of the aqueous polymerization medium (mmol / min·L) is 5.0 × 10 -4 The polymerization method is as follows, wherein the temperature at the start of polymerization is less than 65°C. 6. The aqueous emulsion polymerization method for PFAE-modified PTFE according to item 5 above, comprising: (i) After at least 15 wt% of the total tetrafluoroethylene (TFE) added to the reaction is polymerized, the temperature is set to 70°C or higher; and / or, (ii) No paraffin wax is used; and / or, (iii) PFAE is added to the polymerization vessel in advance before adding the initiator, the aforementioned polymerization method. [Advantageous Effects of the Invention]

[0009] According to the present invention, · A modified PTFE fine powder suitable as a raw material for a PTFE porous membrane having a small pore size and high porosity, · The aqueous emulsion polymerization method for PTFE thereof, · A PTFE porous membrane obtained from the PTFE fine powder are provided. [Modes for Carrying Out the Invention]

[0010] The modified PTFE of the present invention is obtained from tetrafluoroethylene (TFE) and perfluoroalkylethylene (PFAE).

[0011] [PFAE] PFAE is a compound having the following structure. CH2=CH-Rf (Rf is a perfluoroalkyl group) The number of carbon atoms in Rf is not limited, but a compound (PFBE) in which the number of carbon atoms is 4, that is, R is a perfluorobutyl group, is particularly preferred. PFAE functions as a nucleating agent for the polymerization reaction of TFE, and among them, PFBE has good reactivity and is utilized in the polymerization reaction at an early stage even when precharged, i.e., added to the polymerization vessel in advance before adding the initiator.

[0012] The content of PFAE in the PTFE particles of the modified PTFE fine powder of the present invention is preferably 0.03 mol% or more. It is more preferably 0.05 mol% or more, and even more preferably 0.07 mol% or more. Further, it is preferably 0.5 mol% or less. If the content of PFAE in the PTFE particles is too low, that is, if the amount of PFAE supplied to the polymerization reaction with TFE is too small, the particle size of the primary particles of the resulting modified PTFE tends to increase, and as a result, fibrillation during stretching of the paste obtained from the modified PTFE fine powder becomes insufficient, which is not preferable as a raw material for a dense porous membrane with a small pore size. In addition, if the content of PFAE is too high, that is, if the amount of PFAE supplied to the polymerization reaction with TFE is too large, the polymerization reaction will be slowed down, and fibrillation during stretching of the paste obtained from the modified PTFE fine powder may be less likely to occur.

[0013] [Polymerization Reaction] As the method for producing the modified PTFE fine powder of the present invention, emulsion polymerization (aqueous emulsion polymerization) using an aqueous medium such as water is preferred.

[0014] Except for the items specifically defined in the present specification, known methods for emulsion polymerization using an aqueous medium can be used. For example, as such a method, the methods described in the following publications are exemplified, but the present invention is not limited thereto. Patent No. 5470044, Patent No. 5588679, Japanese Patent National Publication No. 2013-542308, Japanese Patent National Publication No. 2013-542309, Japanese Patent National Publication No. 2013-542310, Japanese Patent National Publication No. 2016-537499, Japanese Patent National Publication No. 2023-543807, Patent No. 5949883, Patent No. 6750729.

[0015] In the aqueous emulsion polymerization of TFE and PFAE of the present invention, · The ratio of the addition rate of the initiator at the start of polymerization (mmol / min) to the volume of the aqueous polymerization medium (L) is 5.0×10 -4 or less, • The polymerization start temperature must be less than 65°C. This is especially important. By defining the process as described in the present invention, the molecular weight of the resulting PTFE primary particles becomes larger. As a result, when the PTFE primary particles are subjected to shear stress such as stretching, fibrillation is more likely to occur, and a porous membrane with a fine porous structure (small average pore diameter) can be obtained.

[0016] • Polymerization initiator The ratio of the addition rate of polymerization initiator at the start of polymerization (mmol / min) to the volume of aqueous polymerization medium (L) is 5.0 × 10⁻⁶. -4 The following, preferably 3.0 × 10 -4 The following, more preferably, 2.0 × 10 -4 The following, and more preferably, 1.55 × 10 -4 The following applies: The addition rate of polymerization initiator at the start of polymerization (mmol / min) refers to the amount of polymerization initiator (mmol) used per minute during the first 5 minutes of the reaction. Furthermore, the volume of the aqueous polymerization medium (L) refers to the volume of the aqueous polymerization medium in which the emulsion polymerization reaction takes place.

[0017] Furthermore, the total amount of polymerization initiator used per kg of PTFE obtained is preferably 0.2 mmol or less, more preferably 0.1 mmol or less, and even more preferably 0.05 mmol or less.

[0018] While commonly used and known initiators can be used as polymerization initiators in aqueous emulsion polymerization, radical polymerization initiators are preferred. From the viewpoint of ease of adjusting the amount of radicals, redox-type initiators are preferably suitable. Specifically, potassium permanganate (KMnO4) is preferably used.

[0019] The polymerization initiator is used as a solution dissolved in an aqueous polymerization medium (generally water), and the concentration of this solution is preferably 0.2 mmol / L or less, more preferably 0.1 mmol / L or less, and even more preferably 0.05 mmol / L or less. If the polymerization initiator concentration is too high, there is a concern that the polymerization reaction may proceed at a high rate locally. Conversely, if the concentration is too low, the polymerization reaction will not start.

[0020] • Reaction temperature The temperature of the aqueous polymerization medium at the start of polymerization is less than 65°C, preferably less than 60°C, more preferably less than 55°C, and even more preferably less than 50°C. If the reaction temperature at the start of polymerization is high, the rate of polymerization initiator consumption increases rapidly, leading to excessive initiator consumption. As a result, the reaction may stop midway, or the polymerization reaction may slow down, resulting in a decrease in the productivity of modified PTFE. In this invention, by lowering the reaction temperature at the start of polymerization, the activity of radicals generated from the polymerization initiator is reduced, making it less likely for these radicals to react with each other and become inactive. This is thought to reduce the formation of low molecular weight modified PTFE. Furthermore, side reactions caused by the use of polymerization initiators are also suppressed.

[0021] It is preferable to raise the reaction temperature to 70°C or higher after at least 15 wt% of the total TFE has been consumed (polymerized). More preferably, it should be raised to 80°C or higher. By doing so, the reaction rate of the outer shell of the generated PTFE primary particles is increased, resulting in the acquisition of PTFE with a higher molecular weight.

[0022] • How to install PFAE For introducing PFAE into the aqueous emulsion polymerization reaction system, pre-charging the entire amount at the beginning is preferable, but pre-charging and injection (continuous injection) may be used in combination. Furthermore, from the perspective of ultimately producing a porous membrane, it is preferable not to use monomers other than TFE and PFAE, as they adversely affect the fiber formation of the modified PTFE produced.

[0023] Paraffin wax In aqueous emulsion polymerization of PTFE, paraffin wax is generally used to prevent the formation of PTFE clumps. However, in the polymerization method of the present invention, it is preferable to carry out polymerization without using paraffin wax. This is because, as mentioned above, in the present invention, the polymerization reaction is started at a relatively low temperature, so general paraffin wax solidifies, and the effect of preventing PTFE agglomeration is not obtained. Furthermore, paraffin wax also acts as a chain transfer agent, making stable polymerization difficult.

[0024] • Nucleating agent In the polymerization method of the present invention, known nucleating agents described in Japanese Patent Publication No. 2013-542308, Japanese Patent Publication No. 2013-542309, Japanese Patent Publication No. 2013-542310, etc., can also be used. For example, Japanese Patent Publication No. 2013-542308 describes a nucleating surfactant as follows: The listed nonionic hydrocarbon surfactants (for example, the Tergitol 15-S series, Tergitol TMN series supplied by Dow Chemical Company, the Pluronic R series, and the Iconol TDA series from BASF) are preferably used. These uses can reduce the formation of PTFE agglutination, which increases when paraffin wax is not used as described above.

[0025] ·Average primary particle size The average particle size of the primary particles of the modified PTFE obtained by the polymerization method of the present invention is preferably 200 nm or less. A smaller average particle size of the modified PTFE primary particles is preferable from the viewpoint of producing a PTFE porous film with a small pore size because it increases the surface area and makes it easier to form fibers during stretching. In addition, a smaller average particle size of the modified PTFE primary particles results in better stability of the modified PTFE aqueous dispersion. On the other hand, the average particle size of the primary particles of modified PTFE is preferably 150 nm or larger, more preferably 170 nm or larger, and even more preferably 180 nm or larger. If the average particle size of the primary particles of modified PTFE is smaller than this, the amount of modified PTFE obtained in one polymerization will be small, which poses a problem in terms of productivity.

[0026] The average particle size of primary particles of modified PTFE in an aqueous dispersion after polymerization can be measured using laser diffraction scattering. Furthermore, it can also be estimated by observing the surface of the modified PTFE fine powder obtained by agglomerating and drying a PTFE dispersion using an electron microscope or similar device.

[0027] [Method for manufacturing fine powder] Known methods can be used to obtain modified PTFE fine powder from the obtained modified PTFE aqueous dispersion. Generally, the method described on page 31 of the Fluororesin Handbook (edited by Takaomi Satokawa, first edition published November 30, 1990) is preferred. The obtained modified PTFE aqueous dispersion is diluted with water to a solid content concentration of 10-20%, and optionally an electrolyte such as an inorganic salt or acid, or a water-soluble organic solvent such as methanol or acetone is added and the mixture is vigorously stirred to agglomerate the modified PTFE primary particles. The aggregates separated from the aqueous phase are then washed and dried to obtain modified PTFE fine powder. Specifically, the method described in paragraph

[0062] of Patent Document 1 is an example.

[0028] [Characteristics of Fine Powder] The modified PTFE fine powder of the present invention is characterized in that the tensile breaking strength (breaking strength of the heated-stretched PTFE bead) of the uniaxially heated-stretched bead obtained by heating the extruded bead obtained from the modified PTFE fine powder and performing a tensile test is 25 N or more. This value is preferably 30 N or more, more preferably 35 N or more, and even more preferably 40 N or more. The fracture strength value of such a heat-drawn PTFE bead is an indicator of the strength of the obtained fine powder, similar to "fracture strength A" used in Patent Document 5.

[0029] The standard specific gravity (SSG) of the modified PTFE fine powder of the present invention is preferably 2.150 or less, and more preferably 2.145 or less. While the SSG is affected by the type and content of the comonomers in the modified PTFE, a smaller SSG tends to indicate a higher molecular weight. Since PTFE with a higher molecular weight is more easily formed into fibers by stretching, high molecular weight PTFE is preferably used in the production of small-pore PTFE porous films.

[0030] [PTFE porous membrane] The modified PTFE fine powder of the present invention is suitable for the production of PTFE porous films with small pore sizes. ru. For the manufacture of PTFE porous membranes, for example, the method described in Patent Document 1 can be used, but is not limited to this. The average pore size of the PTFE porous membrane of the present invention is preferably 0.15 μm or less, and more preferably 0.14 μm or less. [Examples]

[0031] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0032] [Various properties] The properties of the obtained modified PTFE fine powder and PTFE porous membrane were measured using the following methods and instruments.

[0033] ·Standard specific gravity (SSG) The standard specific gravity of PTFE was determined according to ASTM D4895.

[0034] ·Average particle size The PTFE dispersion (aqueous dispersion) obtained by polymerization was measured using a laser diffraction / scattering particle size distribution analyzer, Nanotrac Wave II EX-150 (manufactured by Microtrac), and the median diameter D50 from the obtained particle size distribution was defined as the average primary particle size.

[0035] • Breaking strength of heat-stretched PTFE bead <Extrusion bead creation> Place 100g of PTFE fine powder, sifted to remove any lumpy components, into a 500ml poly bottle. Add 22g of the extrusion aid (lubricant) Isopar E to the poly bottle and mix by rolling for 5 minutes. Allow the mixed polymer to mature at a storage room at 25°C for at least 8 hours. Using a rheometer (model: ESE-428-10) manufactured by Toyo Hydraulic Machinery Co., Ltd., the above mixture is filled into a pre-forming cylinder with an inner diameter of 28 mm, and a load of 50 kg is applied to a piston inserted into the cylinder and held for 1 minute to obtain a cylindrical pre-formed product. The obtained pre-formed product is placed in a cylinder (inner diameter 31.7 mm) equipped with an extrusion die (orifice diameter: 1.58 mm, introduction angle: 30°, land length: 15.1 mm) that has been preheated to 45°C, and the above mixture is extruded at a ram speed of 8 mm / min to obtain a string-like material (extrusion bead).

[0036] <Uniaxial heating stretching operation> A section of the extruded bead, 40-80 cm from the tip of the extrusion end, is cut and heated in an explosion-proof dryer at 150°C for 2 hours to remove any remaining extrusion aid. A test piece 25.80 mm long is cut from the heated extruded bead and placed in a tensile testing machine (Tensilon RTC1310A, manufactured by A&D Co., Ltd.) with the ends clamped in a jig. The distance between the jigs is 8.4 mm. After standing in the heating device at 250°C for 10 minutes, a tensile test is performed at a tensile speed of 500 mm / min to obtain a uniaxially heated stretched bead.

[0037] <Fracture Strength Measurement> The obtained uniaxially heated and stretched bead is measured for tensile breaking strength using a tensile tester (the same as above) at room temperature. The conditions at this time were an initial bead length of 50 mm and a tensile speed of 300 mm / min, and the breaking strength detected at this time was used as the measured value.

[0038] · Core / shell ratio The core / shell ratio was calculated with the amount of TFE charged during the period from the start of the polymerization reaction to the completion of the charging of the initiator solution taken as the core weight, and the amount of TFE charged during the period from the completion of the charging of the initiator solution to the stop of stirring taken as the shell weight.

[0039] · Average pore size of PTFE porous membrane The average flow path diameter obtained by measurement in accordance with ASTM F316-86 using a through-pore diameter evaluation apparatus (Porolux 1000 manufactured by Microtrac BEL) was defined as the average pore size. As the test liquid used for the measurement, "GALPORE" (surface tension 16.33 dyn / cm) manufactured by POROMETER was used.

[0040] <Production of PTFE fine powder> [Example 1] A 4-liter stainless steel (SUS316) autoclave equipped with a stirring blade and a temperature control jacket was charged with 2000 ml of deionized water, 12 g of ammonium salt of fluoromonoether acid (formula C3F7-O-CF(CF3)COOH), and 0.05 g of ammonium salt of fluoropolyether acid (C3F7-O-[CF(CF3)CF2]n-CF(CF3)COOH), 0.75 g of succinic acid and 0.026 g of oxalic acid were charged in 50 ml of an aqueous solution, the system was purged three times with nitrogen gas while heating to 80°C to remove oxygen, and then evacuation was performed. Thereafter, 1 g of perfluorobutylethylene (PFBE) was added, the internal pressure was adjusted to 2.75 MPa with tetrafluoroethylene (TFE), and the internal temperature was maintained at 45°C while stirring at 111 rpm.

[0041] Next, an aqueous solution of 10 mg of potassium permanganate (KMnO4) dissolved in 2000 ml of water was injected using a pump at a rate of 13.0-14.0 g / min. The start of the polymerization reaction was defined as the point when the internal pressure dropped by 0.05 MPa. The time required from the injection of the potassium permanganate (KMnO4) aqueous solution to the start of the polymerization reaction was 19.9 minutes. From this point, TFE was continuously added to maintain the internal pressure at 2.75 MPa. As the addition of TFE began, the injection rate of the potassium permanganate aqueous solution was changed to 10.0 ml / min. When the injection of 425 g of potassium permanganate aqueous solution was completed, the internal temperature was raised to 75°C, and TFE was continued to be supplied. At this point, the amount of TFE added since the start of the polymerization reaction was 97 g. When the amount of TFE added since the start of the polymerization reaction reached 308 g, stirring was stopped. The gas inside the autoclave was released to atmospheric pressure, a vacuum was created, and then the pressure was returned to atmospheric pressure with nitrogen gas before the contents were removed and the reaction was terminated.

[0042] The solid content of the obtained PTFE dispersion was 15.6% (460g of modified PTFE), and the average particle size of the primary particles was 0.197 μm. The time required from the start to the end of the polymerization reaction was 75 minutes. Next, the obtained dispersion was diluted with water until the solid content reached 15%, and mechanical stirring was continued at room temperature until the aggregated secondary particles were separated by mechanical stirring. The resulting aggregated secondary particles (PTFE powder) were separated and taken out, and dried at 150°C for 2 hours to obtain PTFE fine powder.

[0043] [Example 2] Polymerization was carried out in the same manner as in Example 1, except that the internal temperature was changed to 85°C after the injection of 425g of potassium permanganate aqueous solution was completed, to obtain a PTFE dispersion. The time required from the injection of potassium permanganate (KMnO4) aqueous solution to the start of the polymerization reaction was 20.2 minutes. The amount of TFE added from the start of the polymerization reaction to the temperature increase was 78g (the amount of TFE added from the start of the polymerization reaction to the cessation of stirring was the same as in Example 1, 308g). The solid content of the obtained PTFE dispersion was 16.3% (476g of modified PTFE), and the average of the primary particles was 16.3%. The particle size was 0.197 μm. The time required from the start to the end of the polymerization reaction was 91 minutes. Using the obtained PTFE dispersion, PTFE fine powder was obtained in the same manner as in Example 1.

[0044] [Example 3] In this experiment, PTFE dispersion was obtained by adding 5 mg of the nonionic surfactant Pluronic 31R1 (BASF) as a nucleating agent to an autoclave, adding 467 g of an aqueous potassium permanganate solution (KMnO4) prepared by dissolving 30 mg of potassium permanganate in 2000 ml of water, and stopping stirring when the total amount of TFE added reached 370 g. The process was carried out in the same manner as in Example 1 to obtain PTFE dispersion. The time required from the injection of the potassium permanganate (KMnO4) aqueous solution to the start of the polymerization reaction was 22.7 minutes. The amount of TFE added from the start of the polymerization reaction until the end of the potassium permanganate aqueous solution addition and heating was 109 g. The solid content of the obtained PTFE dispersion was 17.0% (518 g of modified PTFE), and the average particle size of the primary particles was 0.172 μm. The time required from the start of the polymerization reaction to the end of the reaction was 150 minutes. Using the obtained PTFE dispersion, PTFE fine powder was obtained in the same manner as in Example 1.

[0045] [Example 4] Polymerization was carried out in the same manner as in Example 2, except that an aqueous potassium permanganate solution (KMnO4) was used, prepared by dissolving 30 mg of potassium permanganate (KMnO4) in 2000 ml of water, and the amount added was changed to 467 g, to obtain a PTFE dispersion. The time required from the injection of the aqueous potassium permanganate (KMnO4) solution to the start of the polymerization reaction was 10.8 minutes. The amount of TFE added from the start of the polymerization reaction until the end of the potassium permanganate solution addition and heating was 123 g (the amount of TFE added from the start of the polymerization reaction until the stopping of stirring was the same as in Example 1, 308 g). The solid content of the obtained PTFE dispersion was 16.2% (446 g of modified PTFE), and the average particle size of the primary particles was 0.182 μm. The time required from the start of the polymerization reaction to the end of the reaction was 37 minutes. Using the obtained PTFE dispersion, PTFE fine powder was obtained in the same manner as in Example 1.

[0046] [Example 5] Polymerization was carried out in the same manner as in Example 1, except that 60g of paraffin wax was placed in the autoclave before the start of polymerization, the internal temperature was changed to 63°C at the start and to 85°C after the completion of potassium permanganate aqueous solution addition, and stirring was stopped when the total amount of TFE added reached 126g, thereby obtaining a PTFE dispersion. The time required from the injection of potassium permanganate (KMnO4) aqueous solution to the start of the polymerization reaction was 20.7 minutes. The amount of TFE added from the start of the polymerization reaction until the completion of potassium permanganate aqueous solution addition and temperature increase was 21g. The solid content of the obtained PTFE dispersion was 5.0% (132g of modified PTFE), and the average particle size of the primary particles was 0.186μm. The time required from the start of the polymerization reaction to the end of the reaction was 200 minutes. The resulting dispersion was not diluted, and mechanical stirring was continued at room temperature until the aggregated secondary particles were separated by mechanical stirring. The resulting aggregated secondary particles (PTFE powder) were separated and taken out, and dried at 150°C for 2 hours to obtain PTFE fine powder.

[0047] [Comparative Example] In the same autoclave as in Example 1, 60g of paraffin wax was added in the same amount of raw materials as in Example 1, and the autoclave was vacuumed in the same manner as in Example 1. Then, 1g of perfluorobutyl ethylene (PFBE) was added, and the internal pressure was increased to 2.7 with tetrafluoroethylene (TFE). The pressure was set to 5 MPa, and the internal temperature was maintained at 63°C while stirring at 111 rpm. Next, an aqueous solution of 40 mg of potassium permanganate (KMnO4) dissolved in 2000 ml of water was injected using a pump at a rate of 13.0-14.0 g / min. The start of the polymerization reaction was defined as the point when the internal pressure dropped by 0.05 MPa. The time required from the injection of the potassium permanganate (KMnO4) aqueous solution to the start of the polymerization reaction was 6.8 minutes. From this point onward, TFE was continuously added to maintain the internal pressure at 2.75 MPa. Once the injection of 510g of potassium permanganate aqueous solution was complete, the internal temperature was raised to 85°C, and TFE was continued to be supplied. At this point, the amount of TFE added since the start of the polymerization reaction was 398g. When the total amount of TFE added since the start of the polymerization reaction reached 740g, stirring was stopped. The gas in the autoclave was released to atmospheric pressure, a vacuum was created, and after returning to atmospheric pressure with nitrogen gas, the contents were removed and the reaction was terminated. The solid content of the obtained PTFE dispersion (aqueous dispersion) was 27.6% (937g of modified PTFE), and the average particle size of the primary particles was 0.240 μm. The time required from the start to the end of the polymerization reaction was 105 minutes. Next, PTFE fine powder was obtained in the same manner as in Example 1.

[0048] Table 1 shows the main reaction conditions for Examples 1-5 and the comparative examples, along with the values ​​from a representative example in Patent Document 5 as a reference.

[0049] [Table 1]

[0050] Table 2 shows the main results obtained regarding PTFE dispersion, primary particles, and fine powder.

[0051] [Table 2]

[0052] <Manufacturing of porous membranes using modified PTFE fine powder> Using the PTFE fine powder obtained in Examples 1-5 and the Comparative Example, Isopar M manufactured by ExxonMobil was added to the total weight to 20%, and the mixture was mixed for 5 minutes using a Turbula shaker manufactured by Willy A. Bachofen AG. After standing at 25°C for 24 hours, the mixture was placed into an 80mm diameter cylinder of a pre-molding machine, the top of the cylinder was covered, and compression molding was performed at room temperature (approximately 15-30°C) at a speed of 50 mm / min to obtain a cylindrical pre-molded product.

[0053] The obtained preform was extruded using an extruder with a reduction ratio of 36, a molding temperature of 50°C, and an extrusion speed of 20 mm / min, using an extrusion die (thickness 1 mm x width 140 mm) to obtain a sheet-like extruded product. The obtained sheet-like extruded product was rolled in the extrusion direction (longitudinal direction) to a thickness of 800 μm using two sets of rolls heated to 50°C, and dried at 200°C for 15 minutes to evaporate and remove the isoper M to obtain a sheet-like rolled product. After that, the sheet-like rolled product was cut into squares (90 mm square).

[0054] Using a biaxial stretching machine (EX10-S5 model, manufactured by Toyo Seiki Seisakusho Co., Ltd.), the square (90mm x 90mm) rolled material was fixed around its perimeter with a chuck (size excluding the chuck gripping area of ​​the biaxial stretching machine: 72mm x 72mm), and the material was successively stretched 10 times in the longitudinal and transverse directions (perpendicular to the longitudinal direction) at a stretching speed (chuck movement speed) of 720mm / sec at a molding temperature of 300°C to obtain a stretched material (size excluding the chuck gripping area of ​​the biaxial stretching machine: 720mm x 720mm) (batch type). Two plates heated to 370°C were then held at a distance of 5mm above and below the stretched material as needed, and after the stretched material was fired, the chucks around it were removed to obtain a porous PTFE film.

[0055] The average pore size of the obtained porous membranes is shown in Table 3.

[0056] [Table 3]

[0057] The results in Table 2 show that the modified PTFE fine powder of the present invention, obtained by appropriately controlling the rate of addition of the polymerization initiator at the start of polymerization and the reaction temperature, had a smaller SSG value compared to the comparative example, which was not controlled in this way. This means that the method of the present invention yielded modified PTFE with a larger molecular weight. Furthermore, the particle size of the primary particles of the modified PTFE of the present invention was smaller than that of the comparative example.

[0058] Furthermore, the modified PTFE fine powder used in the production of the porous membrane of the present invention had a higher fracture strength of the heat-stretched PTFE bead than the one used in the production of the porous membrane of the comparative example. This means that the porous membrane of the present invention has a small average pore diameter and a dense structure. As can be seen from the results in Table 3, the average pore size of the porous film obtained by stretching the modified PTFE fine powder of the present invention, which was obtained by appropriately controlling the rate of addition of the polymerization initiator at the start of polymerization and the reaction temperature, was smaller than that of the modified PTFE fine powder obtained without such control (comparative example).

[0059] The results in Tables 2 and 3 confirm that the modified PTFE fine powder of the present invention is optimal for producing PTFE porous membranes with small pore sizes. [Industrial applicability]

[0060] The present invention provides a modified PTFE fine powder suitable for providing PTFE porous membranes with small pore sizes, and a new method for producing such modified PTFE, by appropriately controlling the rate of addition of the polymerization initiator and the reaction temperature at the start of polymerization.

Claims

1. A modified polytetrafluoroethylene (PTFE) fine powder comprising tetrafluoroethylene (TFE) and 0.03 to 0.50 mol% of perfluoroalkylethylene (PFAE), characterized in that the tensile strength of the heat-stretched PTFE bead is 25 N or more.

2. The modified PTFE fine powder according to claim 1, wherein the standard specific gravity (SSG) is 2.150 or less.

3. The modified PTFE fine powder according to claim 1, wherein the average primary particle size is 150 to 200 nm.

4. A modified polytetrafluoroethylene porous membrane comprising tetrafluoroethylene (TFE) and perfluoroalkylethylene (PFAE), wherein the modified polytetrafluoroethylene porous membrane comprises the modified PTFE fine powder described in claim 1.

5. A method for aqueous emulsion polymerization of perfluoroalkylethylene (PFAE)-modified polytetrafluoroethylene (PTFE), wherein the ratio of the initiator addition rate (mol / min) at the start of polymerization to the volume (L) of the aqueous polymerization medium (mol / min·L) is 5.0 × 10⁻⁶. -4 The polymerization method is as follows, wherein the temperature at the start of polymerization is less than 65°C.

6. A method for aqueous emulsion polymerization of PFAE-modified PTFE according to claim 5, (i) After at least 15 wt% of the total tetrafluoroethylene (TFE) added to the reaction has polymerized, the temperature is raised to 70°C or higher; and / or, (ii) Not using paraffin wax; and / or, (iii) The polymerization method wherein PFAE is added to the polymerization tank beforehand before the initiator is added.

Citation Information

Patent Citations

  • Polymerization of tetrafluoroethylene

    JP2000143707A

  • Polytetrafluoroethylene resin

    JP2000143727A

  • Tetrafluoroethylene-perfluorobutylethylene copolymer

    JP2005506405A

  • Porous membrane prepared by stretching heat-treated sheet comprising polytetrafluoroethylene and / or modified polytetrafluoroethylene

    JP2022117687A

  • Aqueous polytetrafluoroethylene emulsion and process for production thereof, aqueous polytetrafluoroethylene dispersion obtained using the emulsion, polytetrafluoroethylene fine powder, and stretch-expanded body

    WO2011055824A1